Kashmir as a borderland : the politics of space and belonging across the line of control - Mato Bouzas, Antía (Asian borderlands, 2019)
This book examines the Kashmir dispute from both sides of the Line of Control (LoC) and within the theoretical frame of border studies. It draws on the experiences of those living in these territories such as divided families, traders, cultural and social activists. Kashmir is a borderland, that is, a context for spatial transformations, where the resulting interactions can be read as a process of "becoming" rather than of "being". The analysis of this borderland shows how the conflict is manifested in territory, in specific locations with a geopolitical meaning, evidencing the discrepancy between "representation" and the "living". The author puts forward the concept of belonging as a useful category for investigating more inclusive political spaces.